The Paris winter - Robertson, Imogen, 1973- (St. Martin's Press, 2014)
"Maud Heighton came to Lafond's famous Academie to paint, and to flee the constraints of her small English town. It took all her courage to escape, but Paris, she quickly realizes, is no place for a light purse. While her fellow students enjoy the dazzling decadence of the Belle Epoque, Maud slips into poverty. Quietly starving, and dreading another cold Paris winter, Maud is hired by Christian Morel as companion to his beautiful, young sister, Sylvie. But Sylvie, Maud discovers, is not quite the darling she seems. She has a secret addiction to opium and an ominous air of intrigue. As Maud is drawn further into the Morels' world of elegant luxury, their secrets become hers. And before the New Year arrives, a greater deception will plunge her into the darkness that waits beneath this glittering city of light. Set against the backdrop of the Great Flood, The Paris Winter is a dark and powerful tale of deceit and revenge from a masterful storyteller."